Demonstrating Technique in Teaching Speaking-Learning Opportunity and Students’ Perception - Muhammad Husnu; Zarwanda Otara Asfarina; Warisatul Aini (LPPM Universitas Bumigora Mataram, 2022)
This paper tries to reveal the influence of Demonstrating techniques on the success of learning English and the concern of students using techniques during the learning process. Quantitative data was carried out experimentally and collected using pre-test, treatment, and post-test techniques, by giving multiple choice tests before and after the application of the techniques. While qualitative data used a questionnaire by giving questionnaires to students, then conducting several interviews related to the application of the techniques. The test results before application of the techniques were only 70% of students who had the ability to speak English, but after the application of the demonstration techniques it increased to 95% of students’ ability to speak English. Meanwhile, in analyzing student perceptions, the study's findings also showed that the demonstration techniques were effective in improving students’ ability in English. The application of the Demonstration techniques in learning English, especially in speaking skill, is the right strategy to improve students’ abilities, because these techniques can turn abstract concepts into reality in the classroom. Keywords: Demonstrating techniques, Learning Opportunity, Students’ Perception